Optimal redundancies of parallel–series systems in irrelevancy coverage model - Xiang, Jianwen; Wang, Zixiang; Wu, Chuanli; Zhao, Dongdong; Tian, Jing (Reliability engineering & system safety, 2022)
A common method for increasing the reliability of a system is to introduce redundant components. However, when the coverage of a fault is imperfect, the system may fail prior to the exhaustion of spares because of noncovered component failures, and an excessive level of redundancy may reduce rather than improve the system reliability. This study investigates the optimal redundancy of parallel–series systems in an irrelevancy coverage model (ICM), which is an extension of the imperfect fault coverage model (IFCM). Three different optimal strategies are studied in ICM, namely optimal redundancies for reliability maximization, cost minimization, and both. Experimental results demonstrate that the optimal redundancies in the ICM are different from those in the IFCM, and the ICM can accommodate more redundant subsystems for parallel–series systems to achieve higher reliability and lower cost than the IFCM in general. •The optimal redundancy of parallel–series systems is addressed in the ICM.•Three types of optimal redundancies for different objectives are studied.•A closed-form solution is provided to evaluate the reliability in the ICM.•The optimal redundancy in the ICM is compared with that in the IFCM.•The results show that the ICM can achieve higher reliability and lower cost.